Propuesta de una Marca Turística para el cantón Macará, provincia de Loja - Cumbicos Alvarado, Lesly Gabriela (2022)
Tourist activity presents a high international competitiveness between countries and cities, for its part, the tourist brands constitute an important initiative since they are capable of promoting tourism, attracting investments, and facilitating the opening of markets for their services and products. The present research work aims to propose a tourist brand for the Macará canton to achieve a better position in the tourist market. To comply with it, three specific objectives are proposed: determine the elements that will constitute the tourist brand for the Macará canton through a diagnosis, propose the design of a tourist brand that transfers the cultural identity of the Macará canton, and propose dissemination strategies and positioning of the tourist brand of the Macará canton. As a methodology for the first objective, a bibliographical review of Macará was made, the survey technique was used to identify and have knowledge of the perception of the inhabitants; The SWOT matrix was used to know what strengths, weaknesses, opportunities, and threats that the brand would present and as a result, the elements that would make up the brand design such as the logo, isotype and slogan were determined. For the second objective, Destination Branding was used as a methodology, which refers to the process by which brands are built; the Adobe Photoshop platform was used to create the visual and graphic elements of the brand from which four designs resulted; A brand test was applied as a technique to local actors to choose the brand that best represents them and later a validation sheet was applied to propose and establish the design that best conveys cultural identity. For the third objective, media were investigated to best place and spread the brand, as a methodology, dissemination strategies were created, resulting in four strategies based on digital and traditional media, public events, and souvenirs; in addition to an estimated budget for compliance and to achieve brand positioning. As a result, the design of a Macará tourist brand was obtained based on methodologies from previous studies that have obtained positive results. This design was proposed to the Tourism and Heritage Department and owners of catering and accommodation establishments as a means to promote tourism in Macará. Concluding that a tourist brand is a valid tool to link the physical elements of the city with the human values of the people, influencing the construction of local cultural identity.